Phenotypic Similarities in Flower Characteristics Between Novel Winter-Hardy Hibiscus Hybrids and Their Tropical Relatives - Malinowski, Dariusz P.; Pinchak, William E.; Yanker-Hansen, Kristin (Frontiers in Plant Science, 2019)
Herbaceous winter-hardy Hibiscus spp. in the section Muenchhusia, also known as rosemallows, are attractive ornamental plants found in temperate environments. These should not be confused with woody winter-hardy hibiscus (Hibiscus syriacus L. and related species) which have also been intensively used as ornamental shrubs. During the past 70 years, breeders have attempted to create winter-hardy hibiscus hybrids with novel flower colors resembling the distantly related tropical Chinese hibiscus, Hibiscus rosa-sinensis L. Although direct attempts to hybridize winter-hardy hibiscus with the tropical hibiscus have been unsuccessful, new interspecific herbaceous winter-hardy hibiscus hybrids with a palette of novel flower colors commonly found in tropical hibiscus have been recently introduced. In this review, we outline the historic perspective on interspecific hybridizations in woody and herbaceous winter-hardy hibiscus and discuss breeding approaches to develop herbaceous winter-hardy hibiscus hybrids with novel flower colors and shapes resembling tropical hibiscus cultivars. By creating a broad genetic variability in herbaceous winter-hardy hibiscus hybrids we found a successful approach to increase the range of flower colors and shapes in these species and made them look very like their distant tropical relatives.